Survey of Consumer Behaviour in Selected International Catering Establishments in Czechia - Kajzar, Patrik; Mura, Ladislav (Communication Today, 2024)
Conducting research in the field of consumer purchasing behaviour gained an attention during the period of the COVID-19 pandemic. The authors of this study decided to focus their attention on selected factors influencing tourism. Since consumer purchasing behaviour is a broad topic, only selected factors that influence tourism demand are addressed. The expected research result is an insight into consumer behaviour in selected international catering establishments in Czechia. Moreover, at a time when the COVID pandemic is slowly fading, purchasing behaviour is becoming increasingly important. The aim of this contribution was to find the factors that most influence the choice of selected tourism facilities in Czechia. Among the key factors that influence the choice of international catering establishments in the Czech Republic, the majority of customers consider the atmosphere of the establishment, the opinion of friends, the right choice of music, and the location of the restaurant as the most important based on their preferences. A more detailed analysis of the survey results revealed that more than one-third of men consider the ability to pay by card to be an important factor that influences their choice of international catering establishments and the right choice of music is moderately important for most respondents in terms of their education. The exceptions to this are respondents with a university diploma who mention the factor of the right choice of music for selecting international catering establishments as the most important.